A case of Perlman syndrome: fetal gigantism, renal dysplasia, and severe neurological deficits - Schilke, Kathrin; Schaefer, Franz; Waldherr, Rüdiger; Rohrschneider, Wiltrud; John, Christoph; Himbert, Urban; Mayatepek, Ertan; Tariverdian, Gholamali (American journal of medical genetics, 2000)
We report on a neonate presenting with polyhydramnios; macrosomia; macrocephaly; visceromegaly including bilateral nephromegaly, hepatomegaly, cardiomegaly; thymus hyperplasia; cryptorchidism; generalized muscle hypotonia; and a distinctive facial appearance. The clinical course was marked by severe neurodevelopmental deficits combined with progressive respiratory decompensation leading to death at the age 6 months. Magnetic resonance imaging (MRI) disclosed a generalized cerebral atrophy with a marked deficit of the white matter. Renal ultrasound and MRI showed markedly enlarged kidneys with multiple small cystic lesions, a pattern indistinguishable from polycystic kidney disease. The postmortem kidney biopsy revealed dysplastic changes, microcysts, and a focal nephrogenic rest, characteristic features of the Perlman syndrome. In children with fetal gigantism, renal abnormalities, and neurological deficits, Perlman syndrome should be considered and may be confirmed by kidney biopsy. Am. J. Med. Genet. 91:29-33, 2000. © 2000 Wiley-Liss, Inc.